Manufacturing method for RTB sintered magnets

JP7604822B2Active Publication Date: 2024-12-24PROTERIAL MAGNETICS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020159280
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-24
Publication Date
2024-12-24
Estimated Expiration
2040-09-24

AI Technical Summary

Benefits of technology

【0014】 本開示によれば、R-T-B系焼結磁石素材に対する溶着が抑制される支持板を用いるため、敷き粉を用いる必要がなくなり、コンタミネーションや装置不具合の発生を抑制しつつ、R-T-B系焼結磁石を製造することが実現し得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604822000003
    Figure 0007604822000003
  • Figure 0007604822000004
    Figure 0007604822000004
  • Figure 0007604822000005
    Figure 0007604822000005
Patent Text Reader

Abstract

To provide a method for manufacturing an R-T-B sintered magnet that eliminates the need for laying powder in a step of diffusing heavy rare earth elements or the like from a diffusion source to a sintered body.SOLUTION: Disclosed is a method for manufacturing an R-T-B based sintered magnet, which comprises a step of preparing an R-T-B based sintered magnet material, a step of preparing diffusion source powders formed from alloy powders containing a heavy rare earth element RH, a step of bringing the diffusion source powders into contact with at least the upper and lower surfaces of the R-T-B based sintered magnet material, a step of placing the R-T-B based sintered magnet material in contact with the diffusion source powders on a support plate, and a diffusion step of performing heat treatment on the R-T-B based sintered magnet material placed on the support plate and diffusing the heavy rare earth element RH contained in the diffusion source powders. The support plate includes at least one kind of first layer selected from the group of MgO, Al2O3, MgAl2O4, CaAlO3 and NdAlO3, and a second layer containing feldspar which crystallizes at 700°C or more, in order from the upper surface, at least on the upper surface side.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an RTB based sintered magnet. [Background technology]

[0002] R2Fe 14 RTB sintered magnets (R is a rare earth element, T is Fe or Fe and Co) with a B-type compound as the main phase are known as the highest performance magnets among permanent magnets, and are used in a variety of motors such as voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV, etc.), motors for industrial equipment, and home appliances.

[0003] RTB sintered magnets are mainly R2Fe 14 It is composed of a main phase made of B-type compounds and a grain boundary phase located at the grain boundaries of the main phase. 14 B-type compounds are ferromagnetic materials with high saturation magnetization and anisotropic magnetic field, and form the basis of the properties of RTB-based sintered magnets. RTB sintered magnets have an intrinsic coercive force H cJ (Hereafter, simply "H cJ In order to avoid irreversible thermal demagnetization, when used in motors, etc., a high H cJ is required to be maintained.

[0004] In RTB sintered magnets, R2Fe 14 When a part of R in the B-type compound phase is replaced with a heavy rare earth element RH (Dy, Tb, etc.), H cJ It is known that the high H cJ In order to obtain this, it is effective to add a large amount of the heavy rare earth element RH to the RTB sintered magnet. However, in an RTB sintered magnet, when the light rare earth elements RL (Nd, Pr) are replaced with the heavy rare earth element RH, H cJ While the residual magnetic flux density B r (Hereinafter, simply "B rIn addition, the heavy rare earth element RH is a scarce resource. For these reasons, there is a demand to reduce the amount of heavy rare earth element RH used.

[0005] Therefore, in recent years, the H of RTB sintered magnets has been developed using less heavy rare earth elements (RH). cJ In order to improve the H of RTB sintered magnets, it has been proposed to supply heavy rare earth elements RH such as Tb and Dy to the surface of the RTB sintered magnet and to diffuse the heavy rare earth elements RH from the surface to the inside of the magnet via the grain boundary phase. This allows the heavy rare earth elements RH to be distributed in large amounts in the outer periphery of the main phase (near the grain boundaries). cJ Since the generation mechanism is of the nucleation type, by distributing a thin shell layer of the heavy rare earth element RH on the outer periphery of the main phase (near the grain boundary), the crystal magnetic anisotropy of the entire crystal grain is enhanced, and the nucleation of reverse magnetic domains is prevented. As a result, cJ In addition, by distributing a thin shell layer (RH-enriched layer) of the heavy rare earth element RH in the outer periphery of the main phase (near the grain boundary), B r The decrease in the amount of the ion exchange resin can be suppressed.

[0006] Patent Document 1 describes a method in which a powder containing Dy, Tb, etc. is present on the surface of an RTB-based sintered magnet material and then heated at a temperature lower than the sintering temperature, thereby diffusing Dy, Tb, etc. from the powder into the interior of the sintered magnet material. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-147634 A Summary of the Invention [Problem to be solved by the invention]

[0008] The diffusion step in which heat treatment is performed with the powder containing Dy, Tb, etc. present on the surface of the RTB-based sintered magnet material can be performed, for example, by conveying a support plate on which a plurality of RTB-based sintered magnet materials are placed into a diffusion heat treatment furnace and heating the RTB-based sintered magnet materials together with the support plate. For this reason, the support plate is made of a material that can withstand the heat treatment temperature (e.g., 700°C or higher) required for diffusion. Specifically, molybdenum and stainless steel are used as the material for the support plate. If the RTB-based sintered magnet material and the support plate are in contact during the heat treatment for diffusion, some of the RTB-based sintered magnet material or the powder attached to the RTB-based sintered magnet material may be fused to the support plate, and the RTB-based sintered magnet material may be damaged when lifted from the support plate. For this reason, a "laying powder" such as alumina powder is spread between the RTB-based sintered magnet material and the support plate to prevent direct contact between the two.

[0009] First, with reference to Figs. 1 to 3, the problems that arise from using a Mo support plate on which a "laying powder" such as alumina powder is spread will be described. Fig. 1 is a perspective view showing a schematic diagram of a Mo support plate 20 on which an RTB based sintered magnet material 10 is placed. Fig. 2 is a cross-sectional view showing a spread powder 40 present between the RTB based sintered magnet material 10 and the Mo support plate 20. 2, a diffusion source powder 30 is attached to the surface of the RTB based sintered magnet material 10. In the diffusion step, the diffusion source powder 30 is melted by heating to a temperature of, for example, 450°C to 1000°C in a heat treatment furnace for diffusion, and the elements contained in the diffusion source powder 30 diffuse from the surface to the inside of the RTB based sintered magnet material 10. The spreading powder 40 serves to prevent the molten diffusion source powder 30 from spreading into the gap between the RTB based sintered magnet material 10 and the Mo support plate 20 and fusing the RTB based sintered magnet material 10 and the Mo support plate 20.

[0010] As described above, if the RTB based sintered magnet material 10 and the Mo support plate 20 are in direct contact with each other during the heat treatment for diffusion, the RTB based sintered magnet material 10 may be welded to the Mo support plate 20, and the RTB based sintered magnet material 10 may be damaged when lifted from the Mo support plate 20. The laying powder 40 serves to suppress or prevent such welding. However, it was found that some of the powder spread on the Mo support plate could become suspended in the air during the manufacturing process or adhere to various devices such as manufacturing equipment and transport devices, which could cause contamination. It was found that this could cause equipment malfunctions and reduce the equipment's operating rate. In addition, there are the following challenges: 3 is a cross-sectional view showing a state in which the RTB-based sintered magnet material 10 is lifted from the Mo support plate 20 after the diffusion step is completed. As shown in FIG. 3, a layer 32 containing a rare earth element R is formed on the surface of the RTB-based sintered magnet material 10, and a part of the spreading powder 40 adheres to the RTB-based sintered magnet material 10. Meanwhile, the spreading powder 40 remaining on the Mo support plate 20 is fixed to the Mo support plate 20 by the molten alloy produced when the diffusion source powder 30 melts. For this reason, the surface of the Mo support plate 20 needs to be cleaned by sandblasting or the like every time the diffusion step is completed. The spreading powder suppresses or prevents such adhesion, and can improve the manufacturing yield of the RTB-based sintered magnets. Thus, there is a need for the development of a support plate that can suppress adhesion between the RTB sintered magnet material and the support plate without using a bedding powder.

[0011] An embodiment of the present disclosure provides a method for producing an RTB based sintered magnet using a support plate that can solve the above problems. [Means for solving the problem]

[0012] In an exemplary embodiment, a method for producing an RTB based sintered magnet according to the present disclosure includes the steps of: preparing an RTB based sintered magnet material (T is Fe or Fe and Co) having, as a main phase, crystal grains of an R2Fe14B type compound containing, as a main rare earth element R, a light rare earth element RL (RL is at least one element selected from the group consisting of Nd, Pr, and Ce); the RTB system sintered magnet material with the diffusion source powder in contact with at least the upper and lower surfaces thereof; and a diffusion step of heat-treating the RTB system sintered magnet material placed on the support plate to diffuse the heavy rare-earth element RH contained in the diffusion source powder from the surface to the inside of the RTB system sintered magnet material, wherein at least the upper surface side of the support plate is provided with a first layer of at least one type selected from the group consisting of MgO, Al2O3, MgAl2O4, CaAlO3, and NdAlO3, and a second layer containing feldspar that crystallizes at 700°C or higher, in that order from the upper surface.

[0013] In one embodiment, the alloy containing a heavy rare earth element RH is an RH-M alloy powder (M is at least one selected from the group consisting of Nd, Pr, Ce, Cu, Ga, Fe, Co, Ni, and Al). Effect of the Invention

[0014] According to the present disclosure, a support plate that is suppressed from welding to the RTB sintered magnet material is used, eliminating the need to use a spreading powder, making it possible to produce RTB sintered magnets while suppressing the occurrence of contamination and equipment malfunctions. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a perspective view that shows a schematic diagram of a Mo support plate on which an RTB based sintered magnet material is placed. [Diagram 2]FIG. 2 is a cross-sectional view showing the powder present between the RTB based sintered magnet material and the Mo support plate. [Diagram 3] FIG. 3 is a cross-sectional view that typically shows the state in which the RTB based sintered magnet material is lifted up from the Mo support plate. [Figure 4] FIG. 4 is a flow chart showing the steps of the method for producing an RTB based sintered magnet in this embodiment. [Diagram 5] FIG. 5 is a cross-sectional view that typically shows the support plate 50 in this embodiment. [Figure 6A] FIG. 6A is a perspective view that typically shows a support plate on which the RTB based sintered magnet material is placed in this embodiment. [Figure 6B] FIG. 6B is a perspective view that typically shows a support frame for stacking support plates in this embodiment. [Figure 7] FIG. 7 is a perspective view that shows a schematic diagram of the state in which the support plate on which the RTB based sintered magnet material is placed and the support frame are stacked in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the present disclosure will be described. A method for producing an RTB based sintered magnet according to an embodiment of the present disclosure includes the following steps, as shown in the flow chart of FIG. A step (S10) of preparing an RTB sintered magnet material (T is Fe or Fe and Co); A step (S20) of preparing a diffusion source powder formed from a powder of an alloy containing a heavy rare earth element RH (RH is at least one selected from the group consisting of Tb, Dy and Ho); a step (S30) of contacting a diffusion source powder with at least the upper and lower surfaces of the RTB based sintered magnet material; a step (S40) of placing the RTB sintered magnet material in contact with the diffusion source powder on a support plate; a diffusion step (S50) of heat-treating the RTB based sintered magnet material placed on a support plate to diffuse the heavy rare-earth element RH contained in the diffusion source powder from the surface of the RTB based sintered magnet material to the inside thereof; Includes.

[0017] Here, the RTB based sintered magnet material is an RFe alloy containing a light rare earth element RL (RL is at least one element selected from the group consisting of Nd, Pr, and Ce) as the main rare earth element R. 14 The RTB based sintered magnet has B-type compound crystal grains as a main phase. Specifically, the light rare earth element RL accounts for 80 mass % or more of the total rare earth element R. In addition, in this disclosure, the RTB based sintered magnet before and during the diffusion step is referred to as the "RTB based sintered magnet material," and the RTB based sintered magnet after the diffusion step is referred to as the "RTB based sintered magnet."

[0018] FIG. 5 is a cross-sectional view showing a schematic diagram of a support plate 50 in this embodiment. The important point of the manufacturing method of the RTB-based sintered magnet of the present disclosure is that, as shown in FIG. 5, at least the upper surface side of the support plate 50 (the upper surface side on which the RTB-based sintered magnet material is placed) is formed with a first layer 70 of at least one kind selected from the group of MgO, Al2O3, MgAl2O4, CaAlO3, and NdAlO3, and a second layer 80 containing feldspar that crystallizes at 700°C or higher, in that order from the upper surface. In the present disclosure, the "second layer containing feldspar that crystallizes at 700°C or higher" refers to a layer containing feldspar that crystallizes by heating to 700°C or higher, for example, SrAl2Si2O8+Al2O3. The second layer 80 is preferably 50 mass% or more of the feldspar. In addition, the first layer 70 is preferably 95% or more of at least one kind selected from the group of MgO, Al2O3, MgAl2O4, CaAlO3, and NdAlO3. The first layer 70 preferably has a thickness of 1 μm or more and 50 μm or less, and the second layer 80 preferably has a thickness of 1 μm or more and 200 μm or less. By using such a support plate 50, it is possible to suppress adhesion between the RTB sintered magnet material and the support plate without using any laying powder.

[0019] The method of forming the first layer 70 and the second layer 80 on the upper surface of the support plate 50 is, for example, as follows. First, a powder having a composition adjusted to form a second layer containing feldspar that crystallizes at 700°C or higher is applied onto the Mo substrate 90 by a known screen printing method. Specifically, a slurry is prepared by kneading 60 mass% of a vehicle in which 5 mass% ethyl cellulose is dissolved in a butyl carbitol acetate solvent and 40 mass% of a specific powder, and the slurry is used as a printing paste. Next, Al2O3 having an average particle size of 5 μm is applied onto the applied paste by a known screen printing method. The slurry is prepared by a method similar to that described above. Note that the application method is not limited to the screen printing method. It may be performed by other known application methods such as a spray method. Then, the paste applied onto the Mo substrate 90 and the support plate 50 to which Al2O3 has been applied are subjected to a heat treatment in an inert gas (for example, in a N2 flow) at 1000°C for 2 hours, thereby forming the first layer and the second layer on the upper surface of the support plate 50. The heat treatment is performed in a state where both the paste and Al2O3 are applied. This allows the Mo substrate 90 and Al2O3 to be firmly attached to each other via a second layer (e.g., SrAl2Si2O8+Al2O3) containing feldspar that crystallizes at 700° C. or higher. The heat treatment temperature is preferably 700° C. or higher and lower than 1100° C., and the heat treatment time is, for example, 1 hour or higher and 10 hours or lower.

[0020] Before describing each of the above steps, an example of the configuration of the support plate in this embodiment will be described. <Example of support plate configuration> Fig. 6A is a perspective view showing a support plate 50 on which the RTB based sintered magnet material 10 is placed in this embodiment, and Fig. 6B is a perspective view showing a support frame 60 for stacking the support plates 50 in this embodiment. Fig. 7 is a perspective view showing a state in which the support plates 50 on which the RTB based sintered magnet material 10 is placed and the support frames 60 are stacked in this embodiment.

[0021] As described above, the support plate 50 in the embodiment of the present disclosure has, at least on the upper surface side, a first layer 70 of at least one type selected from the group consisting of MgO, Al2O3, MgAl2O4, CaAlO3, and NdAlO3, and a second layer 80 containing feldspar that crystallizes at 700°C or higher, which are formed in this order from the upper surface. MgO, Al2O3, MgAl2O4, CaAlO3, and NdAlO3 have low reactivity with the metal elements contained in the RTB based sintered magnet material 10 and the diffusion source powder 30, and are chemically stable. Therefore, by forming at least one first layer selected from the group consisting of MgO, Al2O3, MgAl2O4, CaAlO3, and NdAlO3 on the upper surface of the support plate 50, it is possible to suppress welding between the RTB based sintered magnet material and the support plate 50. However, if the support plate 50 is formed only from the first layer 80, the adhesion strength to the substrate 90 (e.g., a Mo substrate) is low and there are many gaps, so that the first layer 70 may be welded to the RTB sintered magnet, or the diffusion source powder may be melted during the heat treatment for diffusion and the diffusion melt layer formed may impregnate the first layer 70, reach the substrate 90, and weld it. To prevent such a situation, the second layer 80 is formed on the upper surface of the substrate 90. The substrate 90 and the first layer 70 can be firmly adhered to each other by the second layer 80. The second layer 80 contains feldspar that crystallizes at 700°C or higher. By using a layer containing feldspar that crystallizes at 700°C or higher as the second layer 80, the first layer 70 that is firmly adhered to the upper surface of the support plate 50 through the second layer 80 can be formed, and even if the diffusion melt layer melts, it will not reach the substrate 90 because the second layer 80 is dense. This makes it possible to suppress adhesion between the RTB sintered magnet material and the support plate without preparing a bedding powder such as Al powder each time a diffusion heat treatment is performed. In addition, since crystallization is completed at or above the crystallization temperature when the second layer 80 is fired, no volume change occurs in the second layer 80 due to the glass-crystallization transition during the heat treatment for diffusion, and the mismatch between the substrate 90 and the second layer 80 is only due to the difference in thermal expansion, so that the material can withstand heat treatment at the diffusion temperature for a long time or during repeated use. The temperature at which the printed film is baked is 700°C or higher so that the second layer 80 is sufficiently crystallized.Also, on the high-temperature side, it is desirable that the temperature be less than 1100°C at which molybdenum oxide melts and deteriorates, so as not to be affected by the surface layer of the substrate 90 oxidized by interface reactions or trace oxygen in the atmosphere. The first layers 70 are all high-melting-point materials with a high binding force to oxygen that are difficult to react with Nd. Although they do not densify with each other during this process, if they are fixed on the substrate via the second layer and can support the diffusion heat-treated magnet sample by point contact, they can serve their purpose, so there is no need to densify them by fixing them to the second layer 80.

[0022] As shown in FIG. 6A, in order to place a large number of R-T-B sintered magnet materials 10 on a single support plate 50, it is desirable to have sufficient mechanical strength to support the total weight of the R-T-B sintered magnet materials 10. For example, when laminating the R-T-B sintered magnet materials 10 as shown in FIG. 7 using the support frame 60 shown in FIG. 6B, it is preferable to minimize the amount of deflection of the support plate 50 as much as possible. The maximum allowable amount of deflection of the support plate 50 is determined so that in the laminated state, the support plate 50 does not contact the R-T-B sintered magnet material 10 located below. Hereinafter, detailed examples of each step will be described.

[0023] <Step of preparing an R-T-B sintered magnet material> An R-T-B sintered magnet material 10 having R2FeB-type compound crystal grains as the main phase and containing a light rare earth element RL (RL is at least one selected from the group consisting of Nd, Pr, and Ce) as the main rare earth element R is prepared. 14 An R-T-B sintered magnet material 10 having R2FeB-type compound crystal grains as the main phase and containing a light rare earth element RL (RL is at least one selected from the group consisting of Nd, Pr, and Ce) as the main rare earth element R is prepared. Known R-T-B sintered magnet materials 10 can be used. For example, it has the following composition. Rare earth element R: 27.5 to 35.0 mass%, B (a part of B (boron) may be substituted with C (carbon)): 0.80 to 1.20 mass%, Ga: 0 to 0.8 mass%, Additive element M (at least one selected from the group consisting of Al, Cu, Zr, and Nb): 0 to 2 mass%, T ((T is Fe or Fe and Co) and inevitable impurities: the balance.

[0024] The rare earth element R mainly contains a light rare earth element RL, but may also contain a heavy rare earth element RH (RH is at least one element selected from the group consisting of Tb, Dy and Ho). The sintered RTB magnet material having the above composition can be manufactured by any known manufacturing method. The sintered RTB magnet material 10 may be in an as-sintered state, or may have been subjected to cutting or polishing. Moreover, the RTB sintered magnet material 10 preferably has a dimension in the thickness direction of 1 mm or more and 5 mm or less. For example, if the magnet is rectangular and has dimensions of 4 mm x 4 mm x 2 mm, the thickness direction is the direction of the smallest dimension, 2 mm. If the dimensions are the same, for example, 2 mm x 2 mm x 2 mm, the thickness direction is 2 mm. If the dimension in the thickness direction is less than 1 mm, cracks or breaks may occur due to insufficient strength, and if it exceeds 5 mm, it may be difficult to sufficiently diffuse the heavy rare earth element RH to the center part of the RTB sintered magnet material 10. Also, the thickness direction does not necessarily have to be the magnetization direction, and the magnetization direction may be a direction different from the thickness direction.

[0025] <Step of preparing diffusion source powder> A diffusion source powder 30 containing a powder of an alloy containing a heavy rare earth element RH (RH is at least one element selected from the group consisting of Tb, Dy and Ho) is prepared. The diffusion source powder 30 is, for example, an RH-M alloy powder (M is at least one selected from the group consisting of Nd, Pr, Ce, Cu, Ga, Fe, Co, Ni, and Al). The method for producing the RH-M alloy powder is not particularly limited. It may be produced by a method of producing an alloy ribbon by the roll quenching method and then pulverizing this alloy ribbon, or by a known atomizing method such as the centrifugal atomizing method, the rotating electrode method, the gas atomizing method, or the plasma atomizing method. The ingot produced by the casting method may also be pulverized. Typical examples of the RH-M alloy powder are DyFe alloy powder, DyAl alloy powder, DyCu alloy powder, TbFe alloy powder, TbAl alloy powder, TbCu alloy powder, DyFeCu alloy powder, TbCuAl alloy powder, TbNdCu alloy powder, DyNdCu alloy powder, TbNdPrCu alloy powder, TbNdCePrCu alloy powder, TbNdGa alloy powder, TbNdPrGaCu alloy powder, etc. Further, the RHM alloy powder preferably contains Cu. By containing Cu, sufficient heavy rare earth element RH can be diffused from the surface layer region to a deeper region (the central portion of the magnet) of the R-T-B system sintered magnet material 10. The particle size of the RH-M alloy powder is, for example, 500 μm or less, and the smaller one is 10 μm or more.

[0026] <Step of bringing the diffusion source powder into contact with the surface of the R-T-B system sintered magnet material 10> After preparing the above-mentioned R-T-B system sintered magnet material 10, the diffusion source powder 30 is brought into contact with at least the upper surface and the lower surface of the R-T-B system sintered magnet material 10. Note that at least the upper surface and the lower surface of the R-T-B system sintered magnet are the lower surface and the upper surface that become the lower side and the upper side in the vertical direction when placed on the support plate. The method of bringing the diffusion source powder 30 into contact with the surface of the R-T-B system sintered magnet material 10 is not particularly limited. For example, the diffusion source powder 30 may be applied to the surface of the R-T-B system sintered magnet material 10 by the spraying method, the dipping method, or a dispenser. Further, an adhesive may be applied to the surface of the R-T-B system sintered magnet material 10, and the diffusion source powder 30 may be scattered on the adhesive.

[0027] In this embodiment, a method of immersing an R-T-B sintered magnet material 10 coated with an adhesive into flowing diffusion source powder, namely a so-called fluidized bed coating process, is used. Any method may be employed to fluidize the diffusion source powder. For example, the diffusion source powder may be placed in a container provided with a porous partition wall at the bottom, and a gas such as air or an inert gas may be pressurized and injected into the container from below the partition wall, and the diffusion source powder above the partition wall may be floated by the pressure or air flow. By immersing (placing or passing through) the R-T-B sintered magnet material 10 coated with an adhesive into the diffusion source powder flowing inside the container, the diffusion source powder can be adhered to the R-T-B sintered magnet material 10. The time for immersing the R-T-B sintered magnet material 10 coated with an adhesive is, for example, about 0.5 to 5.0 seconds. According to the fluidized bed coating process, since the diffusion source powder is fluidized (stirred) in the container, it is possible to suppress the phenomenon that relatively large powder particles are biased and adhered to the magnet surface, or conversely, relatively small powder particles are separated and adhered to the magnet surface. Therefore, the diffusion source powder 30 can be adhered to the R-T-B sintered magnet material 10 more uniformly.

[0028] <Step of placing the R-T-B sintered magnet material on the support plate> As shown in FIG. 7, a plurality of RTB-based sintered magnet materials 10 with the diffusion source powder 30 attached to the surface are placed on a support plate 50 and stacked via a support frame 60. The shapes of the support plate 50 and the support frame 60 are not limited to the example shown in the figure. From the viewpoint of increasing mass productivity, it is preferable that the support plate 50 is supported from below by the support frame 60 outside an area (support area) wider than a rectangular area of, for example, 100 mm long x 50 mm wide. The size of the support area can be expanded beyond a rectangular area of ​​400 mm long x 150 mm wide if the thickness of the support plate 50 is, for example, 4 mm or more. By adopting such a configuration, the number of RTB-based sintered magnet materials 10 that can be mounted per layer can be sufficiently increased. On the other hand, the support plate 50 is required to realize a sufficiently small deflection in such an area. According to the embodiment of the present disclosure, due to the heat resistance and strength of Mo, even a support plate 50 having the above-mentioned area can be realized with a relatively thin thickness (preferably 3 mm or less). Alternatively, a relatively thin support plate made of alumina may be placed on a plate made of molybdenum or stainless steel, and a plurality of RTB sintered magnet materials with the diffusion source powder attached thereto may be placed on the support plate.

[0029] <Diffusion process> The RTB based sintered magnet material 10 mounted on the support plate 50 as described above is subjected to a heat treatment. Specifically, the heat treatment is performed by heating for at least one hour at a temperature of 450°C or higher and lower than the sintering temperature of the RTB based sintered magnet material 10. This heat treatment allows the heavy rare earth element RH contained in the diffusion source powder 30 to diffuse from the surface to the inside of the RTB based sintered magnet material 10. If the heating temperature is lower than 450°C, the amount of liquid phase containing the heavy rare earth element RH will be too small, resulting in insufficient diffusion into the inside of the RTB based sintered magnet and a high H cJ In addition, if the heat treatment temperature for diffusion exceeds the sintering temperature, abnormal grain growth occurs, and B r and H cJ The heat treatment temperature for diffusion is preferably 850°C or higher and 950°C or lower. By performing diffusion in this temperature range, a higher H cJThe heat treatment can be carried out using a known heat treatment device.

[0030] As described above, by carrying out the heating for one hour or more, the heavy rare earth element RH can be diffused to the outer periphery of the main phase (near the grain boundaries) in the surface region of the RTB sintered magnet, and the heavy rare earth element RH can be diffused from the surface region of the magnet to a region deeper inside (the center part of the magnet). r High H cJ It is possible to obtain an RTB based sintered magnet having the above properties. The heating time in the diffusion process of the present disclosure starts when the temperature of the RTB based sintered magnet material 10 reaches a set temperature (for example, when the set temperature is 920°C, it is 920°C) and ends when the temperature drops below the set temperature by more than 20°C (for example, when the set temperature is 920°C, it is less than 900°C). The temperature of the RTB based sintered magnet material 10 can be measured, for example, by attaching a thermocouple to the RTB based sintered magnet material 10. The heating time is preferably 8 hours or more and 45 hours or less, and more preferably 10 hours or more and 36 hours or less.

[0031] After the diffusion step, the RTB sintered magnet may be subjected to a second heat treatment for the purpose of improving its magnetic properties. The temperature, time, and other conditions in the second heat treatment may be those known as heat treatment conditions for sintered magnets (for example, 500°C for 3 hours or more). The final magnet dimensions may be adjusted by machining such as grinding. In this case, this may be done before or after the second heat treatment. The support plate 50 may be used as is during the second heat treatment.

[0032] According to the embodiment of the present disclosure, even when the above-mentioned diffusion process is performed, adhesion between the RTB based sintered magnet material 10 and the support plate 50 is suppressed or prevented. In addition, since the laying powder is not required, the above-mentioned problem is solved. EXAMPLES

[0033] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto.

[0034] (Preparing RTB sintered magnet material) The RTB sintered magnet material was weighed out so as to have the composition shown by symbol 1-A in Table 1, and cast by strip casting to obtain flake-shaped raw alloy with a thickness of 0.2 to 0.4 mm. The obtained flake-shaped raw alloy was subjected to hydrogen pulverization, and then subjected to a dehydrogenation treatment in which it was heated in a vacuum to 550°C and then cooled to obtain coarsely pulverized powder. Next, zinc stearate was added as a lubricant to the obtained coarsely pulverized powder in an amount of 0.04 mass% relative to 100 mass% of the coarsely pulverized powder, and mixed. After that, it was dry-pulverized in a nitrogen gas stream using an airflow pulverizer (jet mill device) to obtain particles with a particle size D 50 The finely pulverized powder (alloy powder) with a particle size of 4 μm was obtained. 50 is the volume center value (volume-based median diameter) obtained by the laser diffraction method using the air flow dispersion method.

[0035] The finely pulverized powder was mixed with zinc stearate (0.05% by mass relative to 100% by mass of the finely pulverized powder) as a lubricant and molded in a magnetic field to obtain a green body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other. The obtained compact was sintered for 4 hours (a temperature was selected at which sufficient densification by sintering would occur) to prepare multiple RTB-based sintered magnet materials (No. 1-A). The density of the obtained RTB-based sintered magnet material was 7.5 Mg / m 3 That was all. Table 1 shows the results for the components of the obtained RTB sintered magnet material. The components in Table 1 were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The oxygen content of the sintered body was measured using a gas fusion-infrared absorption method, and it was confirmed to be around 0.1 mass%. The RTB sintered magnet material No. 1-A was then cut and machined into a 4.4 mm x 10.0 mm x 11.0 mm rectangular parallelepiped (the 10.0 mm x 11.0 mm face was the face perpendicular to the orientation direction, and the 4.4 mm direction was the thickness direction, which was the orientation direction).

[0036] [Table 1]

[0037] (Preparing the diffusion source powder) A diffusion source powder was prepared by atomizing an alloy powder having the composition shown in No. 1-a of Table 2. The particle size of the obtained diffusion source powder was 106 μm or less.

[0038] [Table 2]

[0039] (Step of contacting the diffusion source powder with at least the upper and lower surfaces of the RTB sintered magnet material) Next, an adhesive was applied to the entire surface of the RTB sintered magnet material No. 1-A in Table 1. The application method was to heat the RTB sintered magnet material to 60°C on a hot plate, and then apply the adhesive to the RTB sintered magnet material by spraying. PVP (polyvinylpyrrolidone) was used as the adhesive. Next, the diffusion source powder No. 1-a in Table 2 was adhered to the RTB sintered magnet material (No. 1-A) coated with the adhesive. The adhesion method was to spread the diffusion source powder in a container and then adhere the diffusion source powder so as to sprinkle it over the entire surface of the RTB sintered magnet material coated with the adhesive.

[0040] (Step of placing the RTB sintered magnet material in contact with the diffusion source powder on a support plate) A Mo plate measuring 100 mm × 50 mm × 2 mm was prepared. A layer containing feldspar that crystallizes at 800°C or higher (SrAl2Si2O8 + Al2O3 in this example) was then formed on the Mo substrate. )SrCO3, Al2O3, and SiO2 were weighed and mixed so that the result was as follows: the mixture was calcined at 800°C, and then pulverized to produce a powder of 1 μm or less. In addition, a vehicle in which 5 mass% ethyl cellulose was dissolved in a butyl carbitol acetate solvent was mixed at 60 mass% and the powder at 40 mass%, to produce a printing paste, which was then applied by a known screen printing method. The applied thickness was 20 um. MgAl2O4 powder with an average particle size of 5 μm was slurried on the applied paste in the same manner as in the previous section, and applied by a known screen printing method. The applied thickness was 5 μm. The paste applied to the Mo substrate and the support plate on which Al2O3 was applied were subjected to a heat treatment of heating at 1000°C for 2 hours in a N2 flow, forming a first layer (MgAl2O4) and a second layer (SrAl2Si2O8+Al2O3) on the upper surface side of the support plate. To remove the powder of the first layer that was not fused to the second layer after the heat treatment, the material was ultrasonically cleaned in pure water and dried with air at 120° C. Then, ten RTB sintered magnet materials with the diffusion source powder in contact with them were placed on the support plate equipped with the first and second layers.

[0041] (Diffusion process) Using a tubular air flow furnace, the RTB sintered magnet material in contact with the diffusion source powder (No. 1-a) was subjected to a heat treatment (diffusion step) at 900°C for 8 hours in reduced pressure argon controlled at 200 Pa. The RTB sintered magnet after the diffusion treatment was then subjected to a second heat treatment at 500°C for 3 hours to obtain an RTB sintered magnet. After the heat treatment, the RTB sintered magnet was checked for adhesion to the support plate, and no adhesion was found. [Explanation of symbols]

[0042] DESCRIPTION OF SYMBOLS 10 RTB sintered magnet material, 20 Mo support plate, 30 diffusion source powder, 50 support plate, 58 upper surface of support plate, 59 lower surface of support plate, 60 support frame, 70 first layer, 80 second layer, 90 substrate

Claims

1. R containing a light rare earth element RL (RL is at least one selected from the group consisting of Nd, Pr and Ce) as a main rare earth element R 2 Fe 14 A step of preparing an R-T-B based sintered magnet material (where T is Fe or Fe and Co) having B-type compound crystal grains as a main phase; preparing a diffusion source powder including a powder of an alloy including a heavy rare earth element RH (RH is at least one selected from the group consisting of Tb, Dy, and Ho); bringing the diffusion source powder into contact with at least the upper and lower surfaces of the sintered R-T-B magnet material; a step of placing the R-T-B based sintered magnet material in contact with the diffusion source powder on a support plate; a diffusion step of heat-treating the sintered R-T-B based magnet material placed on the support plate to diffuse the heavy rare-earth element R contained in the diffusion source powder from the surface to the inside of the sintered R-T-B based magnet material; A method for producing an R-T-B based sintered magnet comprising the steps of: The support plate is made of, at least on the upper surface side, MgO, Al 2 O 3 , MgAl 2 O 4 , CaAlO 3 and NdAlO 3 and a second layer containing feldspar that crystallizes at 700° C. or higher.

2. 2. The method for producing an R-T-B based sintered magnet according to claim 1, wherein the alloy containing the heavy rare earth element RH is an RH-M alloy powder (M is at least one element selected from the group consisting of Nd, Pr, Ce, Cu, Ga, Fe, Co, Ni, and Al).

Citation Information

Patent Citations

  • Manufacturing method of rare earth permanent magnet

    JP2008147634A

  • Method of manufacturing r-t-b-based sintered magnet, and tool for RH diffusion treatment

    JP2011204965A

  • Bulk RH diffusion source

    JP2013207134A

  • Method for manufacturing r-t-b based sintered magnet

    JP2018026390A

  • Grain boundary diffusion treatment jig and container for grain boundary diffusion treatment jig

    US20160276100A1